Language control in auditory bilingual comprehension: uncovering novel evidence from the n − 2 repetition paradigm - Hong Liu; Adel Chaouch-Orozco (Language and Cognition)
In language production, inhibitory control is assumed to be the primary mechanism responsible for successful bilingual processing. To convey messages in one language, bilinguals must inhibit the unintended language. However, it remains unclear whether the same mechanism works in bilingual comprehension. Following up and expanding on Declerck and Philipp (2018, ‘Is inhibition implemented during bilingual production and comprehension? n–2 language repetition costs unchained’, Language, Cognition and Neuroscience, vol. 33, pp. 608–617), the present study investigates whether inhibition is involved in the linguistic identification system during bilingual comprehension with the n − 2 repetition paradigm. This is the second study exploring comprehension with this methodological setup to date. We used an auditory word–picture matching task with Chinese late trilinguals who learned their two non-native languages (L2 English and L3 Spanish) via formal school instruction. Our results indicate that participants responded faster in the n − 2 repetition trials (i.e., when the target language in the n and n − 2 trials matched). That is, we observed an n − 2 repetition benefit effect, a novel finding in this literature that goes counter the n − 2 repetition cost effect reported in previous studies using production-based tasks. In addition, our results underscore the complex interplay between proficiency and use and the resulting dynamics within the bilingual lexicon. We discuss the results in light of the different bilingual representation and processing models.